Gender mainstreaming in the Kalahi CIDSS national community driven development program an assessment. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication examines the effectiveness of a community driven development program promoting women participation and empowerment in the Philippines.Initiatives of the Kapit Bisig Laban sa Kahirapan Comprehensive and Integrated Delivery of Social Services National Community Driven Development Program were aligned with the gender action plan. The challenges and constraints observed in the program serve as lessons to enhance gender mainstreaming initiatives in community driven development projects and programs.
Keywords: Community development -- Philippines; Community development -- Evaluation; Electronic books